Zygnematalean zygospores: morphological features and use in species identification - Poulícková, A; Zizka, Z; Hasler, P; Benada, O (Folia microbiologica, 2007)
Suitable morphological characteristics for identification of zygnematalean algae were determined using a combination of classical light microscopy (LM) techniques, fluorescence microscopy (with blue and green excitation), scanning electron microscopy (SEM) and specialized culture methods. Characteristics of spore germination, growth and reproduction under culture conditions identified Zygnema chalybeo-spermum in a mixture of zygnematalean spores collected from a small fishpond in Czechia. Reproduction in general, particularly aplanospore formation and lateral conjugation was more frequent and occurred earlier in a nutrient poor medium than in a nutrient rich medium, where vegetative growth was more vigorous. Variability in spore size was wide and influenced by the origin (sexual and/or asexual) of the spores. Asexual spores, particularly partenospores were rounded and significantly smaller than sexual ones. Thus spore morphology alone (size and shape) is not a particularly helpful characteristic for species identification. The mesospore of mature spores contained lipids and a sporopolenin-like material (algaenan), which showed green autofluorescence with blue excitation. The mesospore ornamentation, the only characteristic found that is suitable for identification purposes, can be observed easily in LM and SEM after exospore removal by KOH treatment. Detailed LM and SEM observations of the zygospores of all Zygnema species thus could provide basic data necessary for the preparation of an atlas and key for species identification which, after completion with molecular methods, brings clarification into the genetic relationships between morphospecies.
Keywords: Spores, Fungal; Species Specificity; spory hub; kultivační média; sladká voda; Water Microbiology; mikrobiologie vody; Microscopy; Česká republika; druhová specificita; Fresh Water; Eukaryota; mikroskopie; Culture Media; Czech Republic